2023
DOI: 10.3390/ijms242417504
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Protein Kinases as Therapeutic Targets—Part II: Peptides as Allosteric Protein Kinase C Modulators Targeting Protein–Protein Interactions

Mulate Zerihun,
Samuel J. S. Rubin,
Shmuel Silnitsky
et al.

Abstract: Human protein kinases are highly-sought-after drug targets, historically harnessed for treating cancer, cardiovascular disease, and an increasing number of autoimmune and inflammatory conditions. Most current treatments involve small molecule protein kinase inhibitors that interact orthosterically with the protein kinase ATP-binding pocket. As a result, these compounds are often poorly selective and highly toxic. Part I of this series reviews the role of PKC isoforms in various human diseases, featuring cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…It should be noted that some allosteric inhibitors are also believed to act on PPI sites, but they inhibit kinase activity, while PKIIs inhibit the interaction between kinases and substrates [172]. Unlike small molecules, peptides exhibit more flexible conformations, higher selectivity, and lower costs than antibodies, making them ideal candidates for inhibiting PPIs [19], as shown in Figure 3c. Short linear peptides, in particular, have advantages in improving drug properties and limiting toxicity.…”
Section: Protein-kinase Interaction Inhibitors (Pkiis)mentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that some allosteric inhibitors are also believed to act on PPI sites, but they inhibit kinase activity, while PKIIs inhibit the interaction between kinases and substrates [172]. Unlike small molecules, peptides exhibit more flexible conformations, higher selectivity, and lower costs than antibodies, making them ideal candidates for inhibiting PPIs [19], as shown in Figure 3c. Short linear peptides, in particular, have advantages in improving drug properties and limiting toxicity.…”
Section: Protein-kinase Interaction Inhibitors (Pkiis)mentioning
confidence: 99%
“…Through computer analysis, Mallick et al identified the key TrkA-binding peptide sequence of NGF and designed a hybrid peptide candidate that blocks the interaction between NGF and TrkA, which showed potential in the treatment of ameloblastoma [176]. Mulate et al used AlphaFold to identify various peptides targeting PKC [19]. It is expected that more peptidebased compounds will enter development and clinical research as PKIIs.…”
Section: Protein-kinase Interaction Inhibitors (Pkiis)mentioning
confidence: 99%
See 1 more Smart Citation